Non custodial measures in the system of social readaptation - Niewiadomska-Krawczyk, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
This article refers to one of the very important issues connected with the system of social readaptation and in particular, the role of non custodial measures within that system. It is focused on the meaning of the term of „readaptation” as well as the concept of a ‟system”. The aim of that article is to ﬁnd out the place and the role of non custodial measures, especially conditional suspension of the execution of the deprivation of liberty, in the system of social readaptation.
Keywords: social readaptation; system of social readaptation; non custodial measures